Transfer phenomena in fluid and heat flows XIII : special topic volume with invited peer-reviewed papers only - Rocha, Luiz (Engineer); Miguel, A. F.; Öchsner, Andreas (Defect and Diffusion Forum Ser., 2021)
Special topic volume with invited peer-reviewed papers only.